Common threshold ratios: Basis for evaluating financial risks on the real estate industry - Mendoza, Andrea Jane L., Cruz, Ramil J., Pascual, Alyssa Jean S., Asesor, Le An D., Saberon, Trevor Glen S., Uy, Cloyd Ashley R. 4 0 16; 5
ABSTRACT: This study aimed to evaluate the financial risks in the real estate industry, and to identify the basis for improving the financial decisions in the real estate industry. This provides the real estate entities with an understanding about how to evaluate the financial risk of their company. In order to evaluate the financial risk of the real estate industry, the researchers conducted a survey through distribution of survey questionnaires as their data gathering method to 140 financial analysts as the sample size from different real estate companies within Makati City. The survey questionnaire contained questions regarding the demographic profile of the respondents, its entity, and its capital structure. This study was conducted in the last semester of the Academic Year 2022-2023. Descriptive and inferential analysis, as well as descriptive and inferential statistics have been employed in completing this study. The data were analyzed using the liquidity, profitability, solvency and efficiency ratios, Financial Analysis Percentage and Frequency Distribution and One Way ANOVA. Several factors and strategies were also identified in the study that have influenced the significant difference between the variants in the profile and the financial performance in terms of liquidity, profitability, solvency and efficiency ratios. KEYWORDS: Liquidity, Profitability, Solvency, and Efficiency Ratios, Financial Risk, Financial Analysis, Financial Performance
Undergraduate Thesis: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2